Experimental investigation of the mechanical properties of Alfas stone - Konstas N. Kaklis; Stelios P. Mavrigiannakis; Zach G. Agioutantis; Emmanouil K. Steiakakis; Foteini K. Stathogianni (Fracture and Structural Integrity)
This paper focuses on the experimental investigation of the mechanical properties of the Alfas natural building stone. Two series of uniaxial compression tests and indirect tensile tests (Brazilian tests) were performed in order to determine the uniaxial compressive strength and the indirect tensile strength respectively. Different sets of cylindrical specimens and circular discs were prepared by varying their geometry in order to examine the size effect on the respective strength values. Also, the size effect was investigated with respect to the calculated intact rock modulus and Poisson’s ratio. All specimens were prepared by following the ISRM suggested methods and the load was applied using a stiff 1600 kN MTS hydraulic testing machine and a 500 kN load cell. Strain was measured using biaxial 0/90 stacked rosettes appropriately attached on each specimen.